3-Iodothyronamine-Mediated Metabolic Suppression Increases the Phosphorylation of AMPK and Induces Fuel Choice Toward Lipid Mobilization - Ju, H.; Shin, H.; Son, C.; Park, K.; Choi, I. (Hormone and Metabolic Research, 2015)
Despite broad medical application, induction of artificial hypometabolism in vitro and its biochemical consequence have been rarely addressed. This study aimed to elucidate whether 3-iodothyronamine (T1AM) induces hypometabolism in an in vitro model with activation of AMP-activated protein kinase (AMPK) and whether it leads to a switch in primary fuel from carbohydrates to lipids as observed in in vivo models. Mouse C2C12 myotube and T1AM, a natural derivative of thyroid hormone, were used in this study. The oxygen consumption rate (OCR) decreased in a dose-dependent manner in response to 0–100 μM T1AM for up to 10 h. Upon 6-h of exposure to 75 μM T1AM, the OCR was reduced to 60 vs. ~ 95% for the control. The intracellular [AMP]/[ATP] was 1.35-fold higher in T1AM-treated cells. RT-PCR and immunoblotting analyses revealed that treated cells had upregulated p-AMPK/AMPK (1.8-fold), carnitine palmitoyl transferase 1 mRNA, and pyruvate dehydrogenase kinase, and downregulated acetyl CoA carboxylase (0.4-fold) and pyruvate dehydrogenase phosphatase. The treated cells had darker periodic acid-Schiff staining with 1.2-fold greater glycogen content than controls. Taken together, the hypometabolic response of myotubes to T1AM was dramatic and accompanied by increases in both the relative abundance of AMP and AMPK activation, and fuel choice favoring lipids over carbohydrates. These results are consistent with the general trends observed for rodent models and true hibernators.
Keywords: adenosine nucleotides; C2C12 myotube; hypometabolism; oxygen consumption; T1AM